2010
DOI: 10.1109/tgrs.2009.2029864
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks for the Prediction of Species-Specific Plot Volumes Using Airborne Laser Scanning and Aerial Photographs

Abstract: Parametric and nonparametric modeling methods have been widely used for the estimation of forest attributes from airborne laser-scanning data and aerial photographs. However, the methods adopted suffered from complex remote-sensed data structures involving high dimensions, nonlinear relationships, different statistical distributions, and outliers. In this context, artificial neural networks (ANNs) are of interest as they have many clear benefits over conventional modeling methods and could then enhance the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 41 publications
0
27
0
4
Order By: Relevance
“…The nonparametric k-most similar neighbor method has been successfully tested for species-specific stand attributes estimation from laser data [9]. In a comparison with k-most similar neighbor and artificial neural network models such as self-organizing map and multilayer perceptron, support vector regression (SVR) turned out to be one of the best suited methods for prediction purposes [10].…”
mentioning
confidence: 99%
“…The nonparametric k-most similar neighbor method has been successfully tested for species-specific stand attributes estimation from laser data [9]. In a comparison with k-most similar neighbor and artificial neural network models such as self-organizing map and multilayer perceptron, support vector regression (SVR) turned out to be one of the best suited methods for prediction purposes [10].…”
mentioning
confidence: 99%
“…It has been reported by several researchers (Lippmann, 1987;Cybenko, 1989) that a single hidden layer should usually be sufficient for most problems, especially for classification tasks. The major efforts were focused on controlling the complexity of the model in order to avoid a too complex model structure which may lead into an over fitted ANN model (Niska et al, 2010).…”
Section: Neural Network (Nn)mentioning
confidence: 99%
“…They demonstrated that using only ALS variables resulted in less accurate estimates compared to using combined ALS and images variables. Niska et al [18] compared the kMSN method with three artificial neural network modeling methods: the multilayer perceptron (MLP), support vector regression (SVR), and self-organizing map (SOM) at the plot and stand level. The results revealed that the SVR and MLP models reached the greatest prediction accuracy, the kMSN a lower accuracy, and the SOM the smallest prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%